Automatically determining the origin direction and propagation mode of high‐frequency radar backscatter. Issue 12 (16th December 2015) - Burrell, Angeline G.; Milan, Stephen E.; Perry, Gareth W.; Yeoman, Timothy K.; Lester, Mark
Abstract: Elevation angles of returned backscatter are calculated at Super Dual Auroral Radar Network radars using interferometric techniques. These elevation angles allow the altitude of the reflection point to be estimated, an essential piece of information for many ionospheric studies. The elevation angle calculation requires knowledge of the azimuthal return angle. This directional angle is usually assumed to lie along a narrow beam from the front of the radar, even though the signals are known to return from both in front of and behind the radar. If the wrong direction of return is assumed, large uncertainties will be introduced through the azimuthal return angle. This paper introduces a means of automatically determining the correct direction of arrival and the propagation mode of backscatter. The application of this method will improve the accuracy of backscatter elevation angle data and aid in the interpretation of both ionospheric and ground backscatter observations. Key Points: HF radar backscatter returns from in front of and behind the radar Elevation angles are used to determine backscatter propagation path Interpretation of ionospheric phenomena improved by the determination of the direction of origin